RSTNCOVID Burns: A multi-centre service evaluation and stakeholder survey of the impact of COVID-19 on burns care in England, Wales and Northern Ireland. Issue 5 (May 2022) - Phillips, Georgina S.A.; Wormald, Justin C.R.; Yoshimura, Ryo; Gardiner, Matthew D.; Rodrigues, Jeremy N.; Collins, Declan P.; ,
Abstract: As the UK entered the first wave of the COVID-19 pandemic, the National Health Service published consensus guidance to the UK burns services advising changes to the acute management of burns to allow the continuation of safe care while protecting limited hospital resources. We aimed to describe the demographics of burns service users, changes to clinical pathways and experiences of the burns team during the first wave of the COVID-19 pandemic. All burns services in the UK were invited to participate in a national collaborative, trainee-led study supported by the Reconstructive Surgery Trials Network. The study consisted of (1) a service evaluation of patients receiving burns treatment during the COVID-19 pandemic; (2) a multidisciplinary team survey. Analyses were descriptive and narrative depending on data types. Collaborators from 18 sites contributed data from burns MDT surveys and 512 patients. Patient demographics were consistent with typical burns patterns in the UK. The delayed presentation occurred in 20% of cases, with 24 patients developing complications. MDT surveys indicated substantial adaptations and challenges as a result of the pandemic. Access to theatres and critical care were limited, yet a comprehensive acute burns service was maintained. Telemedicine was utilised heavily to reduce patient footfall. Adaptations in the provision of burns care, including greater outpatient care and telemedicine, have emerged out of necessity with reported success. The impact of reduced scar therapy and psychological interventions for burns patients during the pandemic requires longer-term follow-up. Lessons from the UK experience can be used to strategise for future pandemics.